Study of peak expiratory flow rate in young smokers in community - Mehta, Bosky M.; Satani, Kalpesh (International Journal Of Community Medicine And Public Health, 2022)
Background: Inhaling of cigarette smoke has sudden effect on airways which causes an inflammation in the peripheral airways. Pulmonary function testing (PFT) provides a quantitative and objective assessment of the physiological derangement associated with pulmonary diseases. A study of PEFR in smokers and non-smokers would provide the necessary data to correlate smoking and the effect on the pulmonary health of smokers. Objectives were to study the effect of smoking on lung functions in apparently healthy young smokers and to measure the PEFR and compare the values between young smokers and non-smokers in the villages surrounding Vadodara District, Gujarat. Methods: It was a cross-sectional comparative study. With convenient sampling of total 60 male subjects which are equally divided into smokers (group A) and non-smokers (group B) group between the ages 17-25 years. The PEFR was measured by Wright’s Mini PulmoPeak Flow Meter. Three readings were taken and best of three was documented. Comparison of PEFR values between smokers and non-smokers was done. Results: The mean PEFR between smokers and non-smokers was group A is 310.00 and group B was 440.00 litres/minute (p value <0.05) and the t value was 7.608 which shows that the PEFR of smokers is significantly lower than non-smokers. Conclusions: The values of PEFR are reduced in smokers compared to non-smokers in young individuals in community and all the values are more decreased with increase in number of cigarettes smoke per day.